10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionThis study explored the life, health, and wellbeing of individuals living in rural and remote Arctic and North Sámi areas.MethodsA novel qualitative design was used, incorporating conversational interviews conducted in a rundprat (circle-talk) format. Data were collected from 55 participants across eight northern and Sámi rural and remote villages and townships, including 38 individual interviews, four focus groups (17 participants), and student field and reflection notes. The study was guided by a students-as-partners framework in which students and staff collaborated as co-researchers. A reciprocal, two-way learning process supported shared inquiry between students, academic researchers, clinicians, and nurse teachers. Through observation and interviews, students explored individual, group, and societal dimensions of rural health, deepening their understanding of both the community and the research process.FindingsThree main themes were identified: (1) Quality of life, (2) The realities (3) 'The Challenges We Face'. The findings reflect both the positive and challenging aspects of living in remote Arctic and North Sámi regions of Norway.ConclusionThis study shows that involving nursing students in collaborative fieldwork can offer valuable perspectives on health and wellbeing in Arctic and North-Sámi areas. While residents chose to remain in these regions for the environment, community, and quality of life; they continue to face significant disparities in health service access alongside experiences of racism and colonial structures. The findings point to an urgent need for improved emergency preparedness and stronger cultural inclusion in remote healthcare.